Assessment of membrane and diffusion behavior of soil-bentonite slurry trench wall backfill consisted of sand and Xanthan gum amended bentonite. (10th September 2022) - Ni, Hao; Shen, Sheng-Qiang; Fu, Xian-Lei; Wang, Chang-Ming; Du, Yan-Jun
Abstract: The diffusion and semi-permeable membrane behavior are significant for evaluating pollution containment effectiveness of soil-bentonite slurry trench wall backfill (referred to as SB backfill) at contaminated sites. In this study, chemico-osmotic tests were performed on xanthan gum amended SB backfill (referred to as XGSB backfill) and conventional SB backfill utilizing zinc nitrate and lead nitrate solutions as tested liquids. The effective diffusion coefficient ( D *), retardation factor ( R d ), and chemico-osmotic efficiency coefficient ( ω ) of the backfills were evaluated. The results revealed that each tested backfill behaved as a semi-permeable membrane material with measured ω ranging from 0.015 to 0.14 and 0.007 to 0.05 when exposed to lead and zinc solutions with concentrations varying from 0.5 to 50 mM, respectively. The ω and R d values for the backfills decreased with increasing concentrations of the tested solutions, while the D * of heavy metal cations increased, regardless of backfill type and tested solution type. Compared to the SB backfill, the ω and R d of the XGSB backfill were higher while the D * was lower. The values of ω, D *, and R d for the XGSB backfill were compared to those for soil-bentonite backfills in previous studies. A linear equation was presented to evaluate the correlation between ω and solute concentration in a semi-logarithmic scale. Finally, the advantages of considering membrane behavior in the design of slurry trench wall was discussed with the aid of an example analysis based on the measured ω and D * for the SB and XGSB backfill. Graphical abstract: Image 1 Highlights: ω and R d decrease while D * increases with increasing source metal concentration. Comparative assessment of ω, D *, R d of soil-bentonite backfills is performed. A linear equation between ω and source metal concentration.